Emerging epigenomic landscapes of pancreatic cancer in the era of precision medicine - Gwen Lomberk; Nelson Dusetti; Juan Iovanna; Raul Urrutia (Nature Communications, 2019)
In pancreatic cancer, the epigenomic landscape can strongly impact the disease phenotype. Here, the authors discuss recent advances in our understanding of pancreatic cancer epigenomics, and how this knowledge can integrate with precision medicine approaches in this lethal disease.